109k views
5 votes
-6x - 5y = 64x + y = 3 what is the solution of each system of equations?

User Qwabra
by
5.3k points

1 Answer

4 votes

Solution

For this case we have the following two equations:

-6x -5y = 6 (1)

4x + y=3 (2)

We can solve from from the second equation and we have:

y= 3-4x (3)

We can replace equation (3) into equation (1) and we got:

-6x - 5(3-4x) = 6

Solving we got:

-6x -15 +20x =6

14x = 21

x = 21/14 = 3/2

And then solving for y we got:

y = 3 -4*(3/2)= 3- 6 = -3

Then the final answer is:

x= 3/2 , y= -3

User Sami Ullah
by
5.1k points